Tax Transparency and the Right to Information: Advancing Fiscal Democracy (Indonesian Tax Justice Review, 2024)
Tax transparency is increasingly recognized as a pillar of fiscal democracy and tax justice. This paper examines Indonesia’s tax transparency reforms, including automatic exchange of information and disclosure policies. Through legal analysis, the study evaluates the balance between taxpayer confidentiality and public accountability. The findings indicate that enhanced transparency strengthens institutional trust and compliance, provided adequate safeguards are in place. This paper contributes to global debates on fiscal democracy by demonstrating how transparency reforms can support equitable taxation in emerging economies. Indonesia’s experience offers policy lessons for integrating transparency into tax governance frameworks worldwide.